C8orf37 is mutated in Bardet-Biedl syndrome and constitutes a locus allelic to non-syndromic retinal dystrophies. (2nd July 2016) - Khan, Arif O.; Decker, Eva; Bachmann, Nadine; Bolz, Hanno J.; Bergmann, Carsten
ABSTRACT: Bardet-Biedl syndrome (BBS) is a pleiotropic and clinically and genetically heterogeneous ciliopathy. Primary features are early-onset retinal dystrophy that is typically rod-cone, obesity, polydactyly, renal abnormalities, hypogonadism, and learning difficulties, but most patients do not present with the full clinical picture. In a BBS patient from a consanguineous marriage we performed next-generation sequencing targeting all known BBS genes and other genes known or hypothesized to cause ciliopathies. While no mutation was present in any of the recognized genes for BBS, we were able to identify the homozygous non-conservative mutation c.529C>T (p.Arg177Trp) in C8orf37 that segregated with the phenotype, affects an evolutionarily highly conserved residue, and is bioinformatically predicted to be pathogenic. The same mutation has been described in unrelated patients with non-syndromic cone-rod dystrophy and other C8orf37 changes were found in individuals with retinitis pigmentosa. We conclude that C8orf37 should be added to BBS screening panels as a probable rare cause of the disease and that individuals with C8orf37 -related retinal dystrophy should be screened for BBS features.